O przedmiocie antropologii ekologicznej. Szkic problematyki - Piontek, Janusz (Polskie Towarzystwo Antropologiczne, 1987)
The main thesis of the article says that definite types of biological structures correspond to definite sociocultural systems. Ecological anthropology investigates the essential relations of these factors.
About the subject of ecological anthropology. An outline of the problem